Necrotizing colitis and neoplasm of the colon - Armand Ugón, César; Parma, Dante; Otazú, Heber; Antúnez, Carlos; Domínguez, Carlos; Yametti, Luis (Cirugía del Uruguay, 1979)
The paper describes a case of abrupt onset of necrotlzing colitis, associated with neoplasm of splenic angle of colon. There was no prior evidence worth mentioning. Clinical picture was very serious, but both pathologic processes were solved simultaneously by a right enlarged hemicolectomy with primary ileocolic anastomosis.